A Bandit Worth Hunting: Pancho Villa and America’s War on Terror in Mexico, 1916-1917 - Neagle, Michael E. (Terrorism and political violence, 2021)
The September 11, 2001, attacks were not the first time that a private, foreign group attacked the United States mainland. Although not referred to as an act of “terrorism” at the time, the March 1916 raid of Francisco “Pancho” Villa and his men on Columbus, New Mexico, was understood by Americans of the early-twentieth century in much the same way. The discourse of the “bandit,” as Villa was widely described at the time, connoted many of the same meanings that we ascribe to terrorists in the twenty-first century — criminality, incivility, and illegitimacy. This rhetoric served to dehumanize Villa and justified U.S. incursions on Mexican sovereignty in its fruitless pursuit of him and his militia. Moreover, Villa’s political motivations for the attack reflect a modern understanding of terrorism. He sought revenge against the Woodrow Wilson administration for withdrawing its support of him during the Mexican Revolution and tried to goad the United States and Mexico into a wider war. His brief invasion nearly succeeded in bringing about his desired result. American understandings and approaches to Villa mirror many of the same strategies that have been used in the modern war on terror.